Melanoma Vagina - Urbina Álvarez, Claudia (2015)
A case of melanoma of the vagina, of rare presentation, diagnosed and treated al Edgardo Rebagliati Martins National Hospital, EsSalud is presented. Age at occurrence, gynecological history, symptoms, localization, histology, extension studies, treatment and evolution are described.